Solid waste recycling: balancing reality and aspiration – a case study of the Martyr's charitable recycling project - Hosam Ali Aldhawi Ashokri; Mohd Hazarel Zairy Mohd Harun; Maghchiche Abdelhak; Mohd Asyadi Azam (Indonesian Journal of Social and Environmental Issues (IJSEI), 2026)
This study highlights the significance of solid waste recycling through an examination of a charitable recycling project for solid waste recycling. The project was undertaken by the Martyr Charitable Association and ran from 2013 to 2020, competitively producing decreases in landfill space requirements as well as cleanliness in the public domain, while generating profits exceeding 30,000 dollars that were directly invested back into afforestation and supporting families in crowding their kitchens. The project was able to more than effectively reduce landfill space requirements while conserving materials, generating profits that funded an even greater return to support additional charitable and environmental projects. This study explores the potential of informal grassroots recycling initiatives in regions with limited infrastructure and low rates of formal recycling. It highlights how such community-driven approaches can contribute to the indicators of Success and Sustainability. In addition, the research established specific links to the United Nations Sustainable Development Goals, clearly articulated in Goals 11 (Sustainable Cities and Communities), 12 (Responsible Consumption and Production), and 13 (Climate Action). This one community model could be used as a guide for future projects to build on the support of communities to improve urban solid waste management in developing countries.